The identification of the differences in the level of the speed abilities and the endurance-speed abilities: a case study from the second league football team - Różycki, Waldemar (Quality in Sport, 2015)
The use of technical-tactical abilities is to a great extent dependent on the condition preparation of the player. In order to obtain the information on the players abilities to perform locomotive tasks a collection of tests and trials is carried out. The aim of the work was to identify the differences in the level of speed abilities and endurance-speed abilities of the players of the second league football club basing on a test including multiple effort tasks of maximum intensity with short-term breaks of the active character (modified Rast Test). The analyzed parameters included: start speed, run speed, speed endurance 1, speed endurance 2. The analysis of the research data has proved that the group varies in the abilities to perform locomotive tasks. The highest level of differences was detected in the parameter of start speed, the lowest in speed endurance 1. The cluster analysis appeared to be a sufficient method of identification of relatively homogenous groups of players.